2005
DOI: 10.1080/1351847042000286676
|View full text |Cite
|
Sign up to set email alerts
|

Hedge fund performance and persistence in bull and bear markets

Abstract: This paper tests the performance of 2894 hedge funds in a time period that encompasses unambiguously bullish and bearish trends whose pivot is commonly set at March 2000. The database proves to be fairly trustable with respect to the most important biases in hedge funds studies, despite the high attrition rate of funds observed in the down market. An original ten-factor composite performance model is applied that achieves very high significance levels. The analysis of performance indicates that most hedge fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(25 citation statements)
references
References 31 publications
2
20
3
Order By: Relevance
“…This reduces our sample to 4,143 hedge funds and 2,015 funds of hedge funds. We require all funds to have at least 24 monthly returns because this is the minimum for calculating meaningful performance measures (see Ackermann et al, 1999;Gregoriou, 2002;Capocci andHübner, 2004, Liang andPark, 2007). 7 Eliminating those 1,844 funds with less than 24 monthly returns reduces our sample to 2,936 hedge funds and 1,378 funds of hedge funds.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces our sample to 4,143 hedge funds and 2,015 funds of hedge funds. We require all funds to have at least 24 monthly returns because this is the minimum for calculating meaningful performance measures (see Ackermann et al, 1999;Gregoriou, 2002;Capocci andHübner, 2004, Liang andPark, 2007). 7 Eliminating those 1,844 funds with less than 24 monthly returns reduces our sample to 2,936 hedge funds and 1,378 funds of hedge funds.…”
Section: Datamentioning
confidence: 99%
“…(1999). Although many hedge funds do not use trend‐following strategies, Capocci et al . (2005) found that the market phase may influence the results.…”
mentioning
confidence: 99%
“…() and Boyson (), find that hedge funds persistently deliver positive alphas out of sample. Other research is more critical, claiming that performance persistence depends upon the measure used (Capocci et al ., ), that performance persistence is attributable to passive investments in illiquid assets (Brandon and Wang, ), and even that performance persistence for top funds does not exist at all (Slavutskaya, ). Recently, Dichev and Yu () document a sharp reduction in buy and hold returns for a very large sample of hedge funds and commodity trading advisors, from 18.7% from 1980 to 1994 to 9.5% from 1995 to 2008.…”
Section: Introductionmentioning
confidence: 99%
“…To conduct the dynamic style analysis, we consider a large set of 33 potential style (investable or replicable) benchmarks selected on the basis of the extant literature on the determinants of hedge fund returns (see the for the complete list of benchmarks). We take the major equity, bond, commodity, real estate, exchange, and interest indices over all the continents (e.g., Capocci, Corhay, and Hübner 2005; Fung and Hsieh 2002). …”
Section: Empirical Applicationmentioning
confidence: 99%